2017
DOI: 10.1007/s11096-017-0493-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dexmedetomidine on cardiac complications in non-cardiac surgery: a meta-analysis of randomized trials

Abstract: Background The cardiac protection of dexmedetomidine (Dex) in peri-operative period of patients with non-cardiac surgery is still controversial. Aim of the Review We aimed to evaluate the influence of Dex on cardiac complications in peri-operative period of non-cardiac surgery by using a meta-analysis. Methods PubMed, Embase, the Cochrane library and Springer databases were searched for relevant studies. Patients in the eligible studies were divided into Dex group and placebo group. Relative risk (RR) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Due to . In contrast, another study suggested that perioperative DEX use in noncardiac surgery did not decrease the risk for cardiac complications or mortality and may increase the risk for hypotension and bradycardia [61]. The inconsistency between the results in cardiac and noncardiac surgery may have been the result of a higher potential for postoperative complications and mortality in cardiac surgery, where DEX was reported to provide protective effects by attenuating excessive inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…Due to . In contrast, another study suggested that perioperative DEX use in noncardiac surgery did not decrease the risk for cardiac complications or mortality and may increase the risk for hypotension and bradycardia [61]. The inconsistency between the results in cardiac and noncardiac surgery may have been the result of a higher potential for postoperative complications and mortality in cardiac surgery, where DEX was reported to provide protective effects by attenuating excessive inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…Although in a different setting of cardiac surgery with a higher incidence of adverse events, a previous study reported that dexmedetomidine reduced 1-year postoperative mortality, and overall complication rates [2]. For non-cardiac surgery, a recent meta-analysis reported no significant difference in postoperative all-cause mortality, myocardial ischemia or infarction [3]. However, in this meta-analysis, only four small randomized trials were included for these outcomes.…”
Section: Abstract Dexmedetomidine · Carotid Endarterectomy · Hemodynamentioning
confidence: 90%
“…High doses of dexmedetomidine may lead to cardiovascular side effects, including bradycardia, hypotension or even cardiac arrest. 17 , 18 The common dose of dexmedetomidine used in anaesthesia induction should be no more than 1.0 μg/kg. 19 , 20 Based on clinical practice, .5 μg/kg sufentanil is generally sufficient to completely inhibit the stress response during anaesthesia induction.…”
Section: Discussionmentioning
confidence: 99%